Adenomatoid odontogenic tumour in the maxilla: a rare benign tumour in an uncommon site - Rao R., Soorya; K. S., Ravi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
We report a case of adenomatoid odontogenic tumor (AOT) in the maxilla in a boy aged 17 years. AOT is an odontogenic tumour arising from the enamel or dental lamina. AOT is rare and it represents 3–7% of all odontogenic tumors. This lesion affects young girls and is associated with an impacted tooth, usually canine. This case is presented to highlight the presentation of the tumour in a male patient and in an uncommon site, the left upper 1st molar. Differentiating this benign tumor from other lesions is difficult before surgical management and histopathological examination is important in accurate diagnosis.